Treatment Options for Nosocomial Ventriculitis/Meningitis: A Case Report and Review of the Literature - Marios Karvouniaris; Zoi Aidoni; Eleni Gkeka; Stella Niki Primikyri; Konstantinos Pagioulas; Elena Argiriadou (Pathogens)
Ventriculo-meningitis or nosocomial meningitis/ventriculitis is a severe nosocomial infection that is associated with devastating neurological sequelae. The cerebrospinal fluid isolates associated with the infection can be Gram-positive or -negative, while the Enterococcus spp. is rarely identified. We report a case of a 68-year-old woman with a past medical history of insulin-dependent diabetes mellitus, hypertension, and coronary artery disease. She was admitted to the intensive care unit following a scheduled sphenoid wing meningioma resection. Her course was complicated with left middle cerebral artery pseudoaneurysm and hemispheric hemorrhage, and an arterial stent and external ventricular drainage catheter were placed. Neurological evaluation showed a minimal conscious state. She presented high fever on the 35th intensive care unit day. Cerebrospinal fluid was sampled and the external ventricular catheter was removed. Enterococcus faecalis was isolated from the culture specimen. The patient received targeted treatment with an ampicillin plus ceftriaxone combination, and a follow-up culture confirmed the pathogen’s eradication. Although she was considered cured, she had a prolonged intensive care unit stay and finally died in the ward two months after the completion of treatment. This case highlights the first reported use of this combination in a severe, non-endocarditis, invasive enterococcal infection, while the review discusses treatment options for nosocomial ventriculitis/meningitis.